2015
DOI: 10.1111/bjh.13367
|View full text |Cite
|
Sign up to set email alerts
|

Pentostatin, cyclophosphamide and rituximab for previously untreated advanced stage, low‐grade B‐cell lymphomas

Abstract: Summary We conducted a prospective phase II trial of pentostatin, cyclophosphamide and rituximab as initial therapy for patients with previously untreated advanced stage low-grade or indolent B-cell lymphomas (iNHLs). Of 83 evaluable patients, 91·6% attained an overall response and 86·8% a complete or unconfirmed complete response. The 3-year progression-free survival (PFS) and overall survival rates were 73% and 93%, respectively. The 3-year PFS rate was significantly different for different diagnoses (P = 0·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…A retrospective analysis of 536 patients with treatment‐naive FL found that CR to initial therapy was associated with improved survival (Bachy et al , ). In our study, CR/CRu occurred more frequently in patients with low serum LDH and β2M levels (Samaniego et al , ). In that group of patients, the high CR rates translated into statistically significant, high PFS and OS rates.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…A retrospective analysis of 536 patients with treatment‐naive FL found that CR to initial therapy was associated with improved survival (Bachy et al , ). In our study, CR/CRu occurred more frequently in patients with low serum LDH and β2M levels (Samaniego et al , ). In that group of patients, the high CR rates translated into statistically significant, high PFS and OS rates.…”
Section: Discussionsupporting
confidence: 60%
“…The drug has provided benefits for CLL and iNHL patients, including improved tolerability, reduced myelosuppression and comparable clinical-response rates (Hensel et al, 2005;Ho & Hensel, 2006;Kay et al, 2007;Shanafelt et al, 2007;Tedeschi et al, 2015). In a singlearm prospective phase II trial, we previously demonstrated that pentostatin combined with cyclophosphamide and rituximab (PCR) was well-tolerated, induced strong responses and supported a favourable short-term toxicity profile in previously untreated patients with advanced-stage iNHL (Samaniego et al, 2015). Given those promising early findings, we now provide an update after a median patient follow-up of 108 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Current guidelines do not list the PCR regimen as one of the regimens for treatment of Waldenstrom's macroglobulinemia/lymphoplasmacytic lymphoma. 10 It is listed as one of the recommended regimens for first-line treatment of CLL in patients who are less than 65 years old without comorbidities.…”
Section: Indicationsmentioning
confidence: 99%
“…[16][17][18][19] The studies reviewed reported mild (grade 1 or 2) nausea in 25% to 31% of patients 7 ; moderate to severe (grade 3 or 4) nausea or vomiting was reported in 2% to 3% of patients, respectively. 1,5,9 Prophylactic antiemetic therapy with a serotonin antagonist is recommended [16][17][18][19] but may not be required in all patients. One group suggests addition of a neurokinin (NK 1 ) antagonist may be appropriate in some patients.…”
Section: Supportive Carementioning
confidence: 99%